Immunomodulatory Effects of Combination Therapy with Bushen Formula plus Entecavir for Chronic Hepatitis B Patients. (13th January 2019) - Ji, Long-Shan; Gao, Qiu-Tian; Guo, Ruo-Wen; Zhang, Xin; Zhou, Zhen-Hua; Yu, Zhuo; Zhu, Xiao-Jun; Gao, Ya-Ting; Sun, Xue-Hua; Gao, Yue-Qiu; Li, Man
Abstract : Aim . To compare the clinical efficacy of the combination therapy with Bushen formula (BSF) plus entecavir (ETV) in naïve chronic hepatitis B (CHB) patients and that in CHB patients with partial virological response to ETV and explore the relevant immunoregulatory mechanism. Materials and Methods . Two hundred and twenty CHB patients were enrolled in the historical prospective cohort study. Patients were categorized into a treatment group (T-Group: combination therapy with BSF plus ETV) and a control group (C-Group: ETV). Patients in T-Group and C-Group were grouped into T1/C1 (treatment-naïve patients) and T2/C2 (patients with partial virological response to ETV). Biochemical assessment, viral load quantitation, and HBV markers were tested. Chinese medicine symptom complex score was evaluated and recorded as well. In addition, peripheral blood mononuclear cells were separated from blood samples in 56 patients and 11 healthy donors. The frequencies of Th1, Treg, and dendritic cells (DCs) and expression levels of PD-1/PD-L1 were examined by flow cytometry. Results . In treatment-naïve CHB patients, complete viral suppression rates in HBeAg(−) patients were higher than those in HBeAg(+) patients in both T and C groups. In patients with partial virological response to ETV, the rate of HBsAg decline ≥ 20% in HBeAg(+) patients of T2-Group was higher than that in HBeAg(+) patients of C2-Group. A significant reduction of Chinese medicine symptom complex score was only observed in T-Group. The study of mechanism showed that, compared with healthy controls, Th1 and DC frequencies were decreased in all CHB patients, while Treg frequency was increased only in treatment-naïve patients. In addition, compared with healthy controls, PD-1 expression levels on Th1 and Treg were increased in all patients and PD-L1 expression levels on DCs were increased only in treatment-naïve patients. In treatment-naïve patients, the combination therapy with BSF plus ETV increased Th1 and DC frequencies and decreased Treg frequency, which was correlated with HBsAg decline. In addition, in patients with partial virological response to ETV, the combination therapy downregulated PD-L1 levels on DCs and the frequency of Treg, which was related with HBsAg decline. Conclusions . In patients with partial virological response to ETV, HBeAg(+) patients tend to achieve ideal effects after the combination therapy with BSF plus ETV, which may correlate with the decrease of Treg frequency and the downregulation of PD-L1 levels on DCs.